PERENCANAAN STRATEGIS SISTEM INFORMASI DAN TEKNOLOGI INFORMASI PADA PT INDOMARCO PRISMATAMA - Naomi Ayu Citra Ning Tyas (JURNAL TEKNOLOGIA, 2021)
The rapid development of information systems and technology in the digital era makes competition increasingly fierce among companies. It makes companies required to make innovations by utilizing information systems and technology to increase business profits opportunities. PT Indomarco Prismatama or Indomaret is one of the companies engaged in the franchise business that should implement an information system and information technology strategy to maximize business profits. This research is to determine business strategy and make strategic planning of information systems and information technology for PT Indomarco Prismatama. This research method is descriptive with a qualitative approach and data collecting which is carried out using previous research literature studies and some news obtained from official websites and proved credibility. The result of this research is to provide a plan for the implementation of information system and information technology requirements which are mapped in McFarlan's portfolio to create an implementation roadmap of information systems and technology for the next three years.